2009
DOI: 10.1111/j.1651-2227.2009.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents, siblings and grandparents in the Neonatal Intensive Care Unit A survey of policies in eight European countries

Abstract: The presence of parents and other family members in European NICUs has improved over a 10-year period. Several barriers, however, are still in place, particularly in the South European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(104 citation statements)
references
References 18 publications
2
95
1
6
Order By: Relevance
“…There is convincing evidence about the positive effects of Kangaroo Mother Care [9][10][11], but studies suggest there are huge differences in the provision of facilities to enable skinto-skin care and parental involvement [12,13]. A recent European survey, for example, found that 100% of included units in Sweden had reclining chairs near babies' cots and 100% had beds for the parents whilst in the UK these figures were 11% and 77% respectively [14].…”
Section: Introductionmentioning
confidence: 99%
“…There is convincing evidence about the positive effects of Kangaroo Mother Care [9][10][11], but studies suggest there are huge differences in the provision of facilities to enable skinto-skin care and parental involvement [12,13]. A recent European survey, for example, found that 100% of included units in Sweden had reclining chairs near babies' cots and 100% had beds for the parents whilst in the UK these figures were 11% and 77% respectively [14].…”
Section: Introductionmentioning
confidence: 99%
“…14,19 The QCC covers the following areas: developmental care practices, policies toward parents, control of environment, and infant pain management. Furthermore, general information about the unit is obtained, such as number of beds and admissions per year.…”
Section: Measurement Of Developmental Carementioning
confidence: 99%
“…La présence des parents est trop souvent limitée [10,11]. L'ouverture des services de néonatologie aux parents reste variable en Europe.…”
Section: Introductionunclassified
“…L'ouverture des services de néonatologie aux parents reste variable en Europe. Une enquête réalisée en 2005 dans dix pays européens [11] montre que si l'ouverture des services aux parents 24 heures/24 est admise dans près de 70 % des unités interrogées, il existe des disparités Nord-Sud importantes : cette politique est quasi universelle dans les pays du Nord de l'Europe alors qu'elle n'est admise que dans environ un tiers des unités espagnoles et italiennes. La France occupait alors une position intermédiaire avec un peu plus de 50 % des unités qui autorisaient la présence des parents 24 heures/24, sans aucune restriction.…”
Section: Introductionunclassified